Effect of shenfu injection on microcirculation in shock patients: A protocol for systematic review and meta-analysis. Issue 43 (23rd October 2020) - Zhang, Xuemei; Guo, Ting; Zhang, Kaichen; Guo, Wenhui; An, Xing; Gao, Peiyang
Abstract: Background: Shock is a major public health problem worldwide. At present, the morbidity and mortality of shock patients are relatively high. Vasomotor dysfunction is 1 of the key pathological aspects of shock. Shenfu injection has been widely used for the treatment of shock in China. Pharmacological studies have suggested that Shenfu injection can reduce peripheral circulation resistance and improve microcirculation. The purpose of this study is to evaluate the effect and safety of Shenfu injection on the microcirculation of patients with shock. Methods: This review summarizes and meta-analyzes randomized controlled trials of Shenfu injection for the treatment of shock.Searched the following electronic databases: PubMed, Cochrane Library, Embase, CNKI, VIP and Wanfang Data. The Cochrane risk assessment tool was used to evaluate the methodological quality of randomized controlled trials. All tests are analyzed according to the standards of the Cochrane Handbook. Review Manager 5.3, R-3.5.1 software and Grading of Recommendations Assessment, Development, and Evaluation pro GDT web solution are used for data synthesis and analysis. Results: This review focuses on the effects of Shenfu injection on the microcirculation of shock patients (blood lactic acid level, arteriovenous oxygen saturation, arteriovenous carbon dioxide partial pressure difference, sublingual microcirculation), 28-day mortality, 28-day ICU hospitalization and adverse reaction rate. Conclusion: This review provides a clear basis for evaluating the impact of Shenfu injection on the microcirculation of shock patients, as well as the effectiveness and safety of the treatment.